Effects of chemical ischemia on purine nucleotides, free radical generation, lipids peroxidation and intracellular calcium levels in C 2C12 myotube derived from mouse myocytes - Boffi, Federico Martín (2002)
To elucidate the mechanisms of ischemia-mediated myopathy using in vitro model, changes of purine nucleotides, membrane lipid peroxidation(TBARS), intracellular calcium ([Ca2+]i)levels, generation of free radicals, and deoxyribonucleic acid (DNA) fragmentation were examined in mouse-derived C2C12 myotubes under the condition with an inhibition of glycolytic and oxidative metabolism as the ischemic condition. In purine nucleotides, intracellular adenosine triphosphate (ATP) and guanosine triphosphate (GTP) concentrations rapidly and significantly decreased after the treatment with ischemia. No remarkable differences were observed in other purine nucleotides, with the exception of inosine monophosphate (IMP) and extracellular hypoxanthine levels, both of which increased significantly during the ischemia. The lactate dehydrogenase activity in culture supernatant of C2C12 myotubes increased significantly from 2 to 4 hr after the ischemia. On the generation of free radicals, no spectrum was detected in supernatants throughout the observation period, whereas supernatant TBARS concentration increased rapidly and significantly after the ischemia. The relative intensity of [Ca2+]i significantly increased after the ischemia. On the fragmented deoxyribonucleic acid(DNA), no TUNEL positive cells was detected in C2C12 myotubes after 1 hr of the ischemia, however the positive cell percentage subsequently increased. From these results, it was suggested that the ischemic condition induced changes of membrane permeability and increase of [Ca2+]i, both of which lead to cell membrane damage, although a free radical generation was not detected. The ischemic condition also induced the release of substrate hypoxanthine for free radical generation and might initiate the apoptotic pathway in C2C12 myotubes.